Determinants of Accounting Fraud Propensity at PT. Sumber Pelita Utama - Christina Santoso; Karsiat Karsiat (Faculty of Economics and Business, Universitas Wahid Hasyim, 2024)
This study aims to examine the effect of accounting information systems, emotional intelligence, work ethics, and superiors' support on the tendency of accounting fraud at PT. Sumber Pelita Utama. The population in this study were employees of PT. Sumber Pelita Utama involved in using the budget, amounting to 41 people. As for the samples in this study are all of the population using the census method because the population is very small. The research was conducted in February 2021, the data were collected using a questionnaire, while the data analysis technique of this study was multiple linear regression analysis. The results of this study indicate that accounting information systems, emotional intelligence, work ethics, and superiors' support have a significant negative effect on the tendency of accounting fraud.